2020
DOI: 10.1111/jiec.13073
|View full text |Cite
|
Sign up to set email alerts
|

Hydrothermal carbonization for sludge disposal in Germany: A comparative assessment for industrial‐scale scenarios in 2030

Abstract: The efficient use of biogenic residues can make a significant contribution to increase resource efficiency. Due to its high energy efficiency, hydrothermal carbonization (HTC) is being discussed as a potentially suitable technology for particularly wet and sludgy biogenic residues. In Germany, however, it has not yet been established at industrial continuous operation. Among others, this is due to missing solutions for the economic treatment of the high organic loads in the liquid by‐product and insufficient k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…The common trend in industrial applications of HTC includes the addition of acids (such as H 2 SO 4 ) to recover P from the liquid product. Even though high recovery rates can be achieved through this scenario (>85%), the costs of acid addition, maintenance, and the clean‐in‐process can reach up to 15% of additional costs from the total sum 120 . For this reason, several economic studies involving P‐recovery from HTC at industrial scales reported results that are less competitive with the traditional methods.…”
Section: Applied P‐recovery From Htcmentioning
confidence: 99%
See 1 more Smart Citation
“…The common trend in industrial applications of HTC includes the addition of acids (such as H 2 SO 4 ) to recover P from the liquid product. Even though high recovery rates can be achieved through this scenario (>85%), the costs of acid addition, maintenance, and the clean‐in‐process can reach up to 15% of additional costs from the total sum 120 . For this reason, several economic studies involving P‐recovery from HTC at industrial scales reported results that are less competitive with the traditional methods.…”
Section: Applied P‐recovery From Htcmentioning
confidence: 99%
“…Even though high recovery rates can be achieved through this scenario (>85%), the costs of acid addition, maintenance, and the clean-in-process can reach up to 15% of additional costs from the total sum. 120 For this reason, several economic studies involving P-recovery from HTC at industrial scales reported results that are less competitive with the traditional methods. For instance, González-Arias et al (2021) showed that the price of hydrochar produced at industrial scale can range from €390/ton to €590/ton depending on the plant size.…”
Section: Industrial Applications Of P-recovery From Htcmentioning
confidence: 99%
“…Because battery cell production is still relatively in its early technological stages, there is much potential to improve efficiency, energy consumption, and corresponding GHG emissions in battery cell production. The study is structured analogously to Reißmann et al (2021). Analogously, four different scenarios that may have a significant impact on improving the energy consumption and corresponding GHG emissions of battery cell production were analyzed (Figure 2):…”
Section: F I G U R Ementioning
confidence: 99%
“…The study is structured analogously to Reißmann et al. (2021). Analogously, four different scenarios that may have a significant impact on improving the energy consumption and corresponding GHG emissions of battery cell production were analyzed (Figure 2): Market‐driven (MD) scenario : In this scenario, the strong growth of the battery cell market, which is expected to reach up to 600% of the current level by 2030 was taken into account (Hettesheimer et al., 2021; Zhou et al., 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The quantities/yields depend on the process parameters as well as on the input material itself [25,26]. A well-functioning, reliable, and economical disposal, respectively, and treatment of the PW is essential for the successful commercialization of the HTC technology [27].…”
Section: Introductionmentioning
confidence: 99%